Reproductive strategy of spiny gurnard Lepidotrigla dieuzeidei Blanc and Hureau, 1973 from the south-eastern Adriatic Sea - Dobroslavić, Tatjana; Conides, Alexis J.; Sulić Šprem, Jadranka; Glamuzina, Branko; Bartulović, Vlasta (2021)
This study provides the first data on the reproductive biology of the spiny gurnard Lepidotrigla dieuzeidei. A total of 1027 individuals were collected monthly from September 2011 to August 2012. The total length of the individuals in the sample ranged from 7.46 cm to 14.62 cm with a female to male ratio of 1 to 0.59. Positive allometric growth was observed for both females (b=3.07) and males (b=3.08). Variations of condition factor were similar in both sexes with mean values of 1.07 for females and 1.01 for males. The fish L. dieuzeidei had a long spawning period extending from November to July based on monthly values of gonadosomatic index. Histological analysis showed that this fish was multiple synchronous developments of ovaries with multiple spawning events. The ovaries were always represented with a group of primary oocytes and a diverse population of vitel-logenic oocytes, each specially recruited during the final stages of maturation in uniform or uneven phases. Batch fecundity was estimated gravimetrically using the hydrated oocyte method and was estimated to be around 558 to 10.230 oocytes per female. L. dieuzeidei is an important by-catch species and data from this study represent a valuable contribution to stock management.
Ovo istraživanje donosi prve podatke o reproduktivnoj biologiji kokotića, Lepidotrigla dieuzei-dei. Ukupno je prikupljeno 1027 jedinki, uzorkovano je mjesečno od rujna 2011. do kolovoza 2012. Ukupna duljina jedinki bila je u rasponu od 7,46 cm do 14,62 cm s omjerom spolova ženke:mužjaci 1:0,59. Pozitivan alometrijski rast zabilježen je i kod ženka (b = 3,07) i kod mužjaka (b = 3,08). Promjene indeksa kondicije bile su slične kod oba spola sa srednjim vrijednostima od 1,07 za ženke i 1,01 za mužjake. Temeljem mjesečnih vrijednosti gonadosomatskog indeksa utvrđeno je da kokotić ima dugo razdoblje mriješćenja, od studenog do srpnja. Histološka analiza pokazala je multipli sinkroni razvoj jajnika s više razdoblja mriješćenja. U jajnicima su uvijek bile zastupljene skupine primarnih oocita i raznovrsni stadiji vitelogenih oocita, koji su regrutirani u posljednjim stadijima sazrijevanja u jednoličnim ili neravnomjernim fazama. Fekunditet je procijenjen gravimetrijski primjenom metode hidratiziranih oocita i iznosi oko 558 do 10230 oocita po ženki. Kokotić je važna vrsta u prilovu i podatci iz ovog istraživanja predstavljaju značajan doprinos upravljanja stockom.
Bibliografija: str. 58-61.
Summary ; Sažetak.
Keywords: Ribe -- Koktić -- Oogeneza -- Spermatogeneza -- Plodnost -- Mriješćenje ribe; Jadransko more